تفاعل إدارة الموارد البشرية مع التغيرات الاستراتيجية في المؤسسة الاقتصادية دراسة حالة المجمع الصيدلاني "صيدال" - مسعودي, رشيدة (جامعة الوادي - University of Eloued, 2022)
تعالج هذه الدراسة كيفية استجابة ادارة الموارد البشرية وتفاعلها في تنفيذ وتطوير استراتيجية المؤسسة، وفي ظل المنافسة التي تواجهها من خلال البحث في ممارسات ادارة الموارد البشرية فيها من حيث توفير الموارد البشرية بالكم والنوع المطلوب، وذلك من خلال دورها الأساسي كمرافق ومستشار للإدارة العليا. ومن خلال دراسة حالة مجمع الصناعي الصيدلاني "صيدال" توصلت الدراسة إلى أنه يجب على إدارة الموارد البشرية أن تعمل على تنفيذ ومواكبة متطلبات الإدارة العليا من حيث التوظيف والتكوين والحفاظ على الموارد البشرية. التي تؤدي في نهاية إلى تحقيق الأهداف الاستراتيجية التي تسطرها المؤسسة في مواجهة التغيرات المحيطة بها. This study addresses how human resources management responds and interacts with the implementation and development of the enterprise's strategy, and in the context of the competition, it faces by researching its human resource management practices in terms of providing human resources with the quantity and type required. Through its core role as an escort and adviser to senior management. Through a case study of the pharmaceutical, industrial complex "Saidal", the study concluded that human resources management must work to implement and keep up with the requirements of senior management in terms of recruitment, composition and preservation of human resources. strategic objectives in the face of the changes surrounding them.
The interaction of Human Resources Management with Strategic Changes in the economic enterprise Case study of the pharmaceutical complex "Saidal”
مقال
Keywords: إدارة الموارد البشرية ; استراتيجية المؤسسة ; الميزة التنافسية ; ثقافة المؤسسة ; الجزائر: Human resources; management enterprise strategy; competitive advantage; enterprise culture.